EFFECTIVENESS OF DOUBLE LUMEN CATHETER WOUND CARE USING 0.9% NaCL, 7.5% CHLORHEXIDINE, 15% CETRIMIDE ON DOUBLE LUMEN CATHETER INFECTION IN REGULAR HEMODIALYSIS PATIENTS - Andita, Heru Firman; Abidin, Zainal; Hamim, Nur (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The high incidence of double lumen catheter infections in Hemodialysis patients requires a solution including wound care using the antiseptic chlorhexidine 7.5% and cetrimide 15%. Objectives: The aim of this study is to identify the effect of double lumen catheter wound care using NaCL 0.9%, Chlorhexidine 7.5%, and Setrimide 15% on double lumen catheter infection in regular hemodialysis patients at Bhayangkara Lumajang Hospital. Methods: The research design used was quantitative research with a PreExperimental One-Group Pretest-Posttest Design approach. The population in this study was hemodialysis patients with double lumen access who meet the inclusion and exclusion criteria, with a sample of 31 respondents. The sampling technique uses accidental sampling. Results: The research results were obtained before wound treatment using NaCL 0.9%, Chlorhexidine 7.5%, and Setrimide 15%. From 31 respondents 12 (38.7%) respondents experienced infection and after wound treatment using NaCL 0.9%, Chlorhexidine 7.5%, and Setrimide 15%. From 31 respondents 7 (22.6%) respondents experienced infection. After statistical tests were carried out using the Willcoxon test, the result was P = (0.025 < α 0.05), which means that there is a significant effect between treating double lumen catheter wounds using Nacl 0.9%, chlorhexidine 7.5 %, and cetrimide 15% against double lumen catheter infections in regular hemodialysis patients.